Vloga medicinske sestre z naprednimi znanji pri zdravstveni obravnavi mladostnikov s samopoškodovalnim vedenjem brez samomorilnega namena - Krnel, Tilen Tej (Obzornik zdravstvene nege, 2019)
Introduction: Mental health in adolescents can be compromised by self-injury behaviors in different forms. The purpose of the research was to identify the specific roles of advanced nurse practitioners in the nursing treatment of non-suicidal self-injury behaviors in adolescents. Methods: Literature review and topic analysis method of selected sources with the development of codes, categories and topic areas were used. The search was performed in the electronic databases of CINAHL, MEDLINE and ERIC with the following search words: self-injury, adolescents and advanced nursing. The two main inclusion criteria were the focus on nursing interventions in self-injury behaviors and the period of adolescence. The topic analysis was conducted in a way of inductive coding, where the coding unit was the main findings from selected sources. Results: The proposed roles of the advanced nurse practitioner in addressing non-suicidal self-injury behavior in adolescents are: specialized clinical assessor, screening program practitioner, promotor of mental health, initial specialized treatment practitioner, specific interventions practitioner, non-suicidal self-injury prevention practitioner, participant in an interdisciplinary team and training. Discussion and conclusion: There is a need for the development of the evidence-based clinical pathway for the management of non-suicidal self-injury behavior in adolescents and for evidence-based nursing interventions. Nurses have a unique position here as adolescents often prefer them to other professionals, which might be of great potential for the development of the advanced practitioner role in addressing adolescents' mental health.
Keywords: adolescenca; adolescence; advanced nursing; duševno zdravje; high-risk behaviors; mental health; napredna zdravstvena nega; presejanje; screening; visoko tvegana vedenja